Multi agent system for traffic simulation in Vietnam - Trần, Tiến Công (2016)
The VTS is a system that allows users to design different road systems as well as to create different simulation scenarios with different agent profiles. It was built in 2010 based on the theory of Agent and Multi Agent System.